If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7a + 6a + 7b + -6b + -10a = 0 Reorder the terms: 7a + 6a + -10a + 7b + -6b = 0 Combine like terms: 7a + 6a = 13a 13a + -10a + 7b + -6b = 0 Combine like terms: 13a + -10a = 3a 3a + 7b + -6b = 0 Combine like terms: 7b + -6b = 1b 3a + 1b = 0 Solving 3a + 1b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1b' to each side of the equation. 3a + 1b + -1b = 0 + -1b Combine like terms: 1b + -1b = 0 3a + 0 = 0 + -1b 3a = 0 + -1b Remove the zero: 3a = -1b Divide each side by '3'. a = -0.3333333333b Simplifying a = -0.3333333333b
| 3x-4.2=9.4 | | 8s-240=72 | | (6x)(3x+2)=y | | B+23m=342 | | -2p+4(1-p)=8p-2(1-p) | | 4+3a=22+a | | 4(5x+2)-8(x-6)=62 | | 2Q+D=48 | | B+10m=147 | | 7g-2h=-9 | | -2-16=3(h-2) | | 90+(5x-6)+3x=180 | | 2x+10-4x=-3 | | 4x+5=(-11) | | Y=5(3x-3)+2 | | 3/4(2x-4) | | B+10m=342 | | lnx^5=1 | | 21x/7-5x=24 | | 5/6(-2)p | | 2y/3-14/15=y/5 | | 27m^3+9m^2-12m-4=0 | | x^(11/19)=3 | | 5/6-2p | | GraphX-8y=9 | | 2x(2x-3)=6+x | | 5(4x-9)-7=5(x-3)+38 | | y^2+12y=-x^2-4x+16 | | 2p+-14p+16p=-4 | | 4.47=log(X) | | 4z-3z=17 | | 16=5h-9 |